2010
DOI: 10.1007/s10450-010-9240-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of chromium(VI) adsorption onto modified activated carbons with respect to analytical application

Abstract: Two different types of modification of activated carbon, by treatment with concentrated solution of HNO 3 and outgassing treatment at high temperature, were studied in order to obtain the most effective adsorption of chromium(VI) ions from water solution. The basic parameters affecting the adsorption capacity of Cr(VI) ions on modified activated carbons were studied in details and the effect of modifications of activated carbons has been determined by studying the initial runs of adsorption isotherms. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…The adsorption mechanism of Pt(IV) on the modified activated carbon is quite different from those of Au(III) or Pd(II) on the same sorbent reported in other studies [35,36]. The XPS studies confirmed that Pt(IV) adsorption onto activated carbon is probably connected with both ion exchange and reduction processes on the activated carbon surface.…”
Section: Xps Study Of Platinum Loaded Carbonsupporting
confidence: 58%
See 1 more Smart Citation
“…The adsorption mechanism of Pt(IV) on the modified activated carbon is quite different from those of Au(III) or Pd(II) on the same sorbent reported in other studies [35,36]. The XPS studies confirmed that Pt(IV) adsorption onto activated carbon is probably connected with both ion exchange and reduction processes on the activated carbon surface.…”
Section: Xps Study Of Platinum Loaded Carbonsupporting
confidence: 58%
“…Activated carbon is characterized by a large surface area, well-developed micro pore structure, high adsorption capacity and high degree of surface reactivity. What is more, the activated carbon surface can be easily modified in several ways to provide varying adsorption capacity and selectivity for different ions [26]. The most important phenomena, which affect the ion adsorption capacity, are ion exchange, nonspecific sorption, redox reactions, surface precipitation and formation of surface chelates.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention that sorption capacity for the DMGC* carbon is much higher when compared with the BSPDI impregnated activated carbon (2.1 mg/g for both ions) (Ghaedi et al, 2008). The great adsorption properties of OC* carbon towards Ni(II) and Co(II) ions are probably caused by the presence of humic acids on its surface, which in the form of Ni(II) and Co(II) complexes can adsorb on the carbon active centers (Dobrowolski and Otto, 2010). Despite excellent sorption capacity, that carbon has not been selected for enrichment of nickel and cobalt ions from certified reference materials because of insufficient selectivity in NO 3 À and Cl À matrix.…”
Section: Equilibrium Isotherm Studymentioning
confidence: 97%
“…treatment with concentrated solution of HNO 3 and outgassing treatment at high temperature, were studied in order to obtain the most effective adsorption of Cr VI ions from solution. 222 The reduction of Cr VI to Cr III and further ion exchange mechanism of adsorption onto oxidizing activated carbon and the surface precipitation to Cr(OH) 3 in case of outgassed activated carbon were found as the main adsorption mechanisms of Cr VI ions onto modified activated carbons. The presence of chlorides and nitrates strongly decreased the adsorption of Cr VI onto outgassing activated carbon.…”
Section: Chromiummentioning
confidence: 99%